Binomial Logistic Regression of Contraceptive Use among Indonesian Multiparous Women: Indonesia Health Survey 2023 - Ariyanti, Rea; Rahayu, Eka Putri; Rahayu, Agustin Putri (Tadulako University, 2025)
Family planning (KB) is an important strategy to reduce maternal mortality by reducing the number of pregnancies and the proportion of high-risk pregnancies, while enabling family planning and improving quality of life. Although data from the Central Statistics Agency (BPS) shows fluctuations, the prevalence of active KB participation in Indonesia is not enough to significantly increase contraceptive use, especially in multiparous women. The purpose of this study was to examine the factors that influence contraceptive use in multiparous women in Indonesia. The study design was cross-sectional using secondary data obtained from the 2023 Indonesian Health Survey (SKI). The analysis focused on data from 14,975 multiparous mothers who had filled out the questionnaire. The dependent variable in this study was contraceptive use. Independent variables included age, education level, occupation, insurance ownership, delivery method, pregnancy risk, and history of labor and postpartum complications. Data were analyzed using binomial logistic regression. The results of the study showed that determinant factors such as education level, occupation, delivery method, and history of delivery complications affected the use of contraceptives in multiparous women in general by only 3.1%, while 96.9% were influenced by other factors not included in this model test. Therefore, targeted interventions are very important, including expanding contraceptive education for highly educated women and increasing flexible access to services for informal sector workers, as well as conducting counseling programs especially for women with a history of surgery or delivery with complications, to ensure optimal use of contraceptives